PENGARUH E-BANKING DAN RISK PROFILE TERHADAP PROFITABILITAS PERBANKAN DI INDONESIA - Anggi Rahma Ativanita; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Technological sophistication in the era of globalization continues to encourage banks to provide the latest breakthroughs through modern lifestyles and easy access to banking services through electronic banking. In its implementation, electronic banking offers several services that can be used by customers, including mobile banking and Automated Teller Machines (ATMs). In line with technological developments, the complexity of banking risks has also increased from a credit perspective due to the Covid-19 pandemic. This study aims to determine the effect of electronic banking and risk profiles on banking profitability in Indonesia within 5 years of observation starting in 2017-2021. The research sample consisted of 5 conventional banks that met the purposive sampling criteria using multiple linear regression methods. Previously, a model specification test was carried out, with the results of the Random Effect Model (REM) as the best model to be used in this study. The data used in this study also passed the classical assumption test. Research results show that the number of ATM and NPL has a significant effect on ROA. Meanwhile, mobile banking has no significant effect on ROA.